On listening to Holocaust survivors : beyond testimony - Greenspan, Henry 1948- (Paragon House, 2010)
"Summarizes thirty years of the author's interviews and re-interviews with the same core group of Holocaust survivors. Survivors' recounting is thus approached, not as one-time testimony, but as the fruit of sustained conversation"--Provided by publisher